Prefilled Order Sentences via Free-Text Search for Community-Acquired Pneumonia: A Prospective Observational Study - Ledger, Thomas S.; Yeung, Sharifa; Su, Yuen; Baysari, Melissa T. (Applied Clinical Informatics, 2025)
There is limited literature on prefilled order sentences, a form of prescription prefilled with dosage, route, and frequency information, and none on their effect in a targeted setting for community-acquired pneumonia, for which reported compliance is poor.Prefilled orders incorporated within computerized provider order entry systems (CPOE) may facilitate compliance guidelines by acting as a form of clinical decision support (CDS), providing a default choice for prescribers. We aim to assess the effect of prefilled order sentences on guideline-compliant prescribing.Prospective observational study featuring introduction of prefilled order sentences relating to community-acquired pneumonia. To assess guideline compliance based on the CURB-65 score, a scoring tool was used to assess the severity of community-acquired pneumonia. A study period of 6 months was chosen based on a sample size of 164 records with power of 80% to detect a 20% change in admissions that had guideline-compliant prescribing.The intervention was implemented on February 28, 2023, and data were extracted 6 months before and 6 months after. A total of 11,682 prescriptions were identified before the intervention, and 14,726 after the intervention. After screening and review, this corresponded to 75 and 53 eligible admissions before and after the intervention, which was lower than the anticipated sample size. The mean age of patients was 76.6 years old (sd. 17.3, range 24–97 years). There was a significant difference between before and after samples in the presence of confusion (17.3% before, and 37.7% after; p = 0.009). There was no significant difference in the other parameters of the CURB-65 score in the before and after patient groups. A mild CURB-65 score was reported in 35% of admissions (n = 45), a moderate score in 26% (n = 33), and a score of severe in 39% (n = 50). Less than half of all admissions (46.9%) had prescriptions that were compliant to antibiotic guidelines. Following the intervention, there was a nonsignificant decrease in overall compliance, with 50.7% of admissions having compliant prescriptions before, and 41.5% after intervention.Although unable to reach our planned sample size, the introduction of prefilled order sentences did not change guideline-compliant prescribing. This likely reflects the fact that prefilled orders do not address more systemic barriers affecting antibiotic use and compliance to guidelines.
Keywords: community-acquired pneumonia; order sentences; prefilled order sentences